ESSENTIALS OF PRICING ANALYTICS tools and implementation with excel. - Haugom, Erik, 1982- ([S.l.] : ROUTLEDGE, 2020)
This book provides a broad introduction to the field of pricing as a tactical function in the daily operations of the firmand a toolbox for implementing and solving a wide range of pricing problems. Beyond the theoretical perspectives offered by most textbooks in the field, Essentials of Pricing Analytics supplements the concepts and models covered by demonstrating practical implementations using the highly accessible Excel software, analytical tools, real-life examples and global case studies. The book covers topics on fundamental pricing theory, break-even analysis, price sensitivity, empirical estimations of price-response functions, price optimisation, markdown optimisation, hedonic pricing, revenue management, the use of big data, simulation, and conjoint analysis in pricing decisions, and ethical and legal considerations. This is a uniquely accessible and practical text for advanced undergraduate, MBA and postgraduate students of pricing strategy, entrepreneurship and small business management, marketing strategy, sales and operations. It is also important reading for practitioners looking for accessible methods to implement pricing strategy and maximise profits. Online resources for instructors include Excel templates and PowerPoint slides for each chapter.
OCLC-licensed vendor bibliographic record.
Keywords: Microsoft Excel (Computer file); Pricing -- Computer programs; Electronic spreadsheets -- Computer programs; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Money & Monetary Policy